The Role of Educational Transformation in the Digital Era in Improving Student Quality - Aditya, Rifqi Qadar; Suranto, Suranto (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
This study illustrates how educational transformation in the digital era plays a significant role in improving the quality of students. Through the utilization of various platforms and digital tools, education becomes more innovative and dynamic. Adaptive learning processes enable the development of skills in line with the needs of the modern job market. The aim of this research is to describe the role of educational transformation in the digital era in enhancing the quality of students. The research employs a qualitative approach with interview, observation, and documentation methods to obtain relevant data related to the research on the role of educational transformation in the digital era in improving the quality of students. The research is conducted in the Accounting Education Program at Muhammadiyah University of Surakarta with three lecturers and three students as informants. Data obtained from informants is further processed using the triangulation technique, involving different sources of data and methods. The steps of data analysis include merging, sampling, recording, data reduction, and drawing conclusions. The research findings indicate that the transformation provides significant opportunities to enrich students' learning experiences. However, challenges such as variations in technology understanding among lecturers and the need for the development of digital competencies in students must be addressed. Strong institutional support, including providing training for lecturers and adequate infrastructure on campus, is acknowledged as key to the successful implementation of these changes. This transformation not only contributes to the improvement of student quality but also encourages collective efforts in overcoming emerging obstacles.